LEGAL REVIEW OF THE IMPLEMENTATION OF CUSTOMARY RIGHTS OF INDIGENOUS COMMUNITIES IN PAPUA AFTER THE REVISION OF THE SPECIAL AUTONOMY LAW - Marinus Suprianto Sakmaf (Awang Long Law Review, 2025)
The Indonesian government issued Law No. 21 of 2001 concerning Special Autonomy (Otsus) for the Province of Papua. This law grants a number of special rights to Papua, with the aim of improving the welfare of the Papuan people and recognizing the uniqueness of the social, cultural, and economic aspects of indigenous peoples in Papua. One of the things highlighted in the Otsus Law is the recognition of the customary rights of indigenous peoples which should be protected and respected. The research method used is the normative legal research method. The results of the study indicate that the revision of the Papuan Otsus Law provides new hope for indigenous peoples in obtaining recognition and protection of their customary rights. However, major challenges in its implementation still exist, especially in terms of proving rights, managing natural resources, and resolving disputes fairly and efforts to ensure that the rights of indigenous peoples are respected and protected must be carried out comprehensively and sustainably.